Integrating gamification to increase users’ engagement to adhere COVID-19 interventions using extended TAM - Afiq Kalana, Mohd Hazim; Junaini, Syahrul Nizam; Jali, Suriati Khartini; Rosmansyah, Yusep; Putri, Atina; Kamal, Ahmad Alif (Indonesian Journal of Electrical Engineering and Computer Science, 2025)
Gamification has shown potential for enhancing motivation and engagement, yet its effectiveness in promoting adherence to COVID-19 preventive measures remains underexplored. With decreasing public attentiveness, this study examines the role of gamification in encouraging compliance with health protocols through an extended technology acceptance model (TAM) and structural equation modeling (SEM). A gamified mobile application was developed, incorporating features such as points, badges, and progress tracking, and was designed to appeal to younger audiences. Data collected from 150 secondary school students in Sarawak, Malaysia, indicated that perceived usefulness, perceived ease of use, and attitude toward the app significantly influenced engagement with COVID-19 preventive measures. Among these factors, perceived usefulness demonstrated the strongest effect on engagement (β = 0.424, t = 4.812, p < 0.001). The findings highlight the potential of gamification to enhance compliance with COVID-19 protocols.